Effect of moisture content and amount of Hexane on in-situ transesterification of jatropha seeds for biodiesel production - Ryan Moulana; . Satriana; M. Dani Supardan; Wirda Aina (Syiah Kuala University, 2013)
The aim of this research is to study in-situ transesterification technique of jatropha seeds for biodiesel production. This research was conducted using a randomized factorial block design consisting of two factors that is moisture content of jatropha seeds (2% and 3%) and amount of hexane that used as a co-solvent (0 ml, 75 ml, 95 ml, 115 ml and 135 ml). The experimental result shows that the highest yieldbiodiesel of 78.72 % obtained at process condition of jatropha seeds moisture content of 2% and amount of hexane of 115 mL. The physico-chemical analysis of biodiesel procured the acid number of 0.35 mg KOH/g, density of 0.89 g/mL and viscosity of 3.04 mm2/ s that meet requirement of Indonesian Nasional StandardNo. 04-7182-2006.